1995
DOI: 10.1074/jbc.270.37.21845
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes of the Mitochondrial F1-ATPase ∊-Subunit Induced by Nucleotide Binding as Observed by Phosphorescence Spectroscopy

Abstract: Changes in conformation of the ⑀-subunit of the bovine heart mitochondrial F 1 -ATPase complex as a result of nucleotide binding have been demonstrated from the phosphorescence emission of tryptophan. The triplet state lifetime shows that whereas nucleoside triphosphate binding to the enzyme in the presence of Mg 2؉ increases the flexibility of the protein structure surrounding the chromophore, nucleoside diphosphate acts in an opposite manner, enhancing the rigidity of this region of the macromolecule. Such c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…This result shows that removal of ATP from the loose non-catalytic site induces the loss of the 2nd Fe(III) equivalent, indicating that the conformational changes produced by the detachment of ATP from the loose non-catalytic site, or by the binding of ATP to such site, modulate the binding of Fe(III) to the second site. In line with this result, is the recent finding that binding of ATP or ADP to such site is most responsible for the different conformations assumed by F~ATPase in the presence of saturating ATP or ADP [19].…”
Section: Atp-dependent Binding Of Fe(ili) Is Reverted By Loose Nucleosupporting
confidence: 63%
See 2 more Smart Citations
“…This result shows that removal of ATP from the loose non-catalytic site induces the loss of the 2nd Fe(III) equivalent, indicating that the conformational changes produced by the detachment of ATP from the loose non-catalytic site, or by the binding of ATP to such site, modulate the binding of Fe(III) to the second site. In line with this result, is the recent finding that binding of ATP or ADP to such site is most responsible for the different conformations assumed by F~ATPase in the presence of saturating ATP or ADP [19].…”
Section: Atp-dependent Binding Of Fe(ili) Is Reverted By Loose Nucleosupporting
confidence: 63%
“…Since it has been reported that phosphate, under conditions comparable to those of Fig. 3, does not produce conformational changes transmitted over long distances [5,19], the spectral changes of the Fe(III)-protein adducts induced by phosphate are attributed to a direct interaction of the anion with the metal ions, implying that one of the two iron-binding sites is located in the proximity of a catalytic site. Nothing may be said concerning the location of the second iron centre.…”
Section: The Binding Of Fe(lll) To F1atpase Is Affected By Saturatingmentioning
confidence: 88%
See 1 more Smart Citation
“…Nucleotide binding changed signals from His-179 and His-200, but not from His-119, although substitution of His-119, located at a long loop opposite the catalytic site, suppressed ATPase activity and thermostability. In an unusual approach it was shown that changes in conformation of the ε-subunit of MF 1 can be observed by the phosphorescence emission of Trp (200). An interesting cross-reconstitution of F 1 from MF 1 or EcF 1 with F 0 -containing but F 1 -stripped membranes of E. coli or heart mitochondria was achieved (201).…”
Section: Other Modulations Of Catalysis and Conformationmentioning
confidence: 99%
“…The ε subunit of the bovine mitochondrial F " complex is a peptide of 50 amino acid residues [3] that has been cloned, sequenced and studied in several laboratories ; however, its functional role is far from clear. It has only been reported that its conformation is sensitive to different nucleotides binding to F " [14] and that its suppression in a yeast mutant promotes an uncoupling between the two sectors F ! and F " [15].…”
Section: Introductionmentioning
confidence: 99%